WOMAN EMPOWERMENT AND GENDER JUSTICE - Bhalsod, Urmila B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
From the ancient times, it has been said that “where woman is worshipped there exists God”. Where the woman is adored or respected (revered) the Gods love to stay there. From Manusmruti period till today everyone has said (considered) woman as Nari to be Narayani and established her to be Goddess. The woman possesses unique status in human societies. It has been said that the God created women when he thought to create excellent creation. God has put strength, emotions and sympathy as well as strong will power in woman and also God has endowed woman with the strength to remain firm and strong in adverse circumstances. The woman is indebted to the almighty God for this invaluable gift given to her by the God. The God has given some or the other speciality in each and every woman and that by creating a woman the creator has given the capacity of producing human being. The creator of the world has given this invaluable gift of reproduction of man to this vary woman. This can not be compared with anything else.